2018
DOI: 10.1016/j.athoracsur.2018.05.022
|View full text |Cite
|
Sign up to set email alerts
|

Automated Titanium Fasteners Versus Hand-Tied Knots: A Randomized Controlled Trial

Abstract: Using the automated fastener to facilitate annuloplasty fixation through a sternotomy resulted in a small procedural time savings (average of 10 s/stitch) that had no overall impact on cardiopulmonary bypass or cross-clamp times but added an average cost of $1,026 to the operation.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
27
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 13 publications
(27 citation statements)
references
References 4 publications
0
27
0
Order By: Relevance
“…Whilst there have been no formal cost analysis studies on the use of Cor‐Knot, there is mild cost increase in valve procedures by $58 per application which may balance out against the total cost savings from reducing the operative times, potential complications, and ICU stay . At present, it is controversial to conclude if Cor‐Knot is economically favorable in cardiac valve surgery . On the other hand, a further important quality of Cor‐Knot is the reportedly reduced learning curve meaning that less experienced surgeons and trainees can attain proficiency quicker and with reduced operative times, ultimately .…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Whilst there have been no formal cost analysis studies on the use of Cor‐Knot, there is mild cost increase in valve procedures by $58 per application which may balance out against the total cost savings from reducing the operative times, potential complications, and ICU stay . At present, it is controversial to conclude if Cor‐Knot is economically favorable in cardiac valve surgery . On the other hand, a further important quality of Cor‐Knot is the reportedly reduced learning curve meaning that less experienced surgeons and trainees can attain proficiency quicker and with reduced operative times, ultimately .…”
Section: Discussionmentioning
confidence: 99%
“…On average, the use of Cor‐Knot has been found to shorten AXT up to 20 minutes in heart valve surgeries . However, total hand‐tied knotting times in AVR and MV surgery are approximately 15 and 5 minutes, respectively . The discrepancy between time savings in total knotting times and AXT is speculated to be a result of Cor‐Knot conferring lower rate of intraoperative complications which require further intervention during the operation .…”
Section: Discussionmentioning
confidence: 99%
“…7,26 Provided training is undertaken, Cor-Knot is associated with a short learning curve, enabling surgeons to quickly and effectively obtain proficiency and integrate its use into their daily practise. 27 This has particular relevance to MIVS, whose technically challenging nature often results in increased operating times, leading many surgeons to favor sternotomy. Cor-Knot may negate this additional operating time, thereby supporting surgeons in the transition from sternotomy to minimally invasive approaches.…”
Section: Indications Benefits and Shortcomings Of Cor-knotmentioning
confidence: 99%
“…11,33 With respect to CPBT and AXT, four of the five studies independently found these times to be reduced by Cor-Knot, a finding that was further supported by a meta-analysis. 6,11,19,27,33,34 30 -RCT Perin et al 9 -PCS Wang et al 9 -RCS Morgant et al 10 -PCS Length of ICU stay No significant difference Lee et al 30 -RCT No significant difference Grapow et al 11 -RCS Plestis et al 24 -RCS Perin et al 19 -PCS Beute et al 32 -RCS Morgant et al 10 -PCS Abbreviations: AXT, aortic cross clamp time; AVR, aortic valve replacement; CPBT, cardiopulmonary bypass time; ICU, intensive care unit; MA, meta-analysis; MV, mitral valve; PCS, prospective cohort study; PPI, permanent pacemaker implantation; PVL, paravalvular leak; RCS, retrospective cohort study; RCT, randomized controlled trial.…”
Section: Cor-knot In Mitral Valve Surgerymentioning
confidence: 99%
See 1 more Smart Citation